2015
DOI: 10.1186/s13028-015-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related variations in bone microstructure of rabbits intramuscularly exposed to patulin

Abstract: BackgroundPatulin, a toxic mold metabolite, has been found as natural contaminant of processed fruits, most notably apples, apple juices and other apple-based products. A number of adverse health effects in humans and animals are associated with patulin intoxication. The current study was performed to analyse possible toxic effects of patulin on femoral bone microstructure in adult rabbits in detail. Fourteen clinically healthy four-month-old rabbits of both sexes (6 males and 8 females) were included in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A study performed on adult rabbits showed a significant impact of the mycotoxin on bone microstructure ( 7 ). Acute or chronic exposure of pregnant mothers to DON shows foetotoxic effects evidenced by skeletal ossification decrease and delayed foetal development ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study performed on adult rabbits showed a significant impact of the mycotoxin on bone microstructure ( 7 ). Acute or chronic exposure of pregnant mothers to DON shows foetotoxic effects evidenced by skeletal ossification decrease and delayed foetal development ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits display less cancellous bone than humans . They have more fragile cortices . Cortical thickness and the diameter of drilled holes contribute to the high complication rate of fracture repair in this species .…”
Section: Rabbits In Bone Research: Where Are We?mentioning
confidence: 99%